2004
DOI: 10.1111/j.1439-0388.2004.00459.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of racing merit of thoroughbred horses in Poland

Abstract: The study aimed at estimating variance components of racing ability traits in thoroughbred horses as a contribution to defining the breeding objective for this breed. Data collected were 12 143 placings at finish (square root) and 8641 earnings (log) won by 1414 horses running in 1693 races over the period of 1998-2001. Age of horses ranged from 2 to 5+ years, and the distances were from 1000 to 3200 m. Horses were from 11 state stables, from private breeders (one collective group), and from foreign breeding (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 6 publications
3
23
2
Order By: Relevance
“…Heritability was between 15-20% for the Log of earnings per race and the ranking value, the repeatability between 30-40%. These results did not differ very much from those obtained in Poland [13] and Germany [3] for similar criteria. The repeatability for the distance when placed was low, 28%, but the heritability, 18% was comparable to the heritability of the ranking value and earnings per race.…”
Section: Discussionsupporting
confidence: 53%
“…Heritability was between 15-20% for the Log of earnings per race and the ranking value, the repeatability between 30-40%. These results did not differ very much from those obtained in Poland [13] and Germany [3] for similar criteria. The repeatability for the distance when placed was low, 28%, but the heritability, 18% was comparable to the heritability of the ranking value and earnings per race.…”
Section: Discussionsupporting
confidence: 53%
“…In any event, in practice, the estimation of effects linked to the trainer and the owner is not always possible, because the majority of trainers and owners only own and train one horse, making their effect undistinguishable from the animal effect. In literature, Sobczynska and Lukaszewicz (2004), Svobodova et al (2005) were not able to estimate the effect of the jockey; however, Oki et al (1995) reported in their study that the talent of the jockey had a significant effect on the race time for different distances and different types of race tracks. In our dataset, the effect of the jockey is difficult to estimate.…”
Section: Effect Of the Non-genetic Parameters On The Different Traitsmentioning
confidence: 99%
“…It is important to note here that the assessment of the genetic value of breeding animals has been applied to racehorses for many years and in many countries (Chico, 1994;Langlois, 1996;Belhajyahia et al, 2003;Langlois and Blouin, 2004;Sobczynska and Lukaszewicz, 2004;Svobodova et al, 2005;Bokor et al, 2007;Bakhtiari and Kashan, 2009;Orhan and Kaygisiz, 2010). In Algeria, no selection program has been put in place and no assessment of the genetic additive value of breeding animals based on the performance of horses has been carried out till now despite the availability of reliable performance data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, generational affects, currency inflation, and often conversion (particularly for historic racing records) as well as race type and length must be taken into consideration, resulting in complex mathematical models (Sobczynska & Lukaszewicz 2004;Park 2011).…”
Section: Introductionmentioning
confidence: 99%